Expanding the clinical and radiological phenotypes of leukoencephalopathy due to biallelic HMBS mutations. Issue 10 (4th June 2021) - Stutterd, Chloe A.; Kidd, Alexa; Florkowski, Chris; Janus, Edward; Fanjul, Miriam; Raizis, Anthony; Wu, Teddy Y.; Archer, John; Leventer, Richard J.; Amor, David J.; Lukic, Vesna; Bahlo, Melanie; et al.
Abstract: Pathogenic heterozygous variants in HMBS encoding the enzyme hydroxymethylbilane synthase (HMBS), also known as porphobilinogen deaminase, cause acute intermittent porphyria (AIP). Biallelic variants in HMBS have been reported in a small number of children with severe progressive neurological disease and in three adult siblings with a more slowly, progressive neurological disease and distinct leukoencephalopathy. We report three further adult individuals who share a distinct pattern of white matter abnormality on brain MRI in association with biallelic variants in HMBS, two individuals with homozygous variants, and one with compound‐heterozygous variants. We present their clinical and radiological features and compare these with the three adult siblings previously described with leukoencephalopathy and biallelic HMBS variants. All six affected individuals presented with slowly progressive spasticity, ataxia, peripheral neuropathy, with or without mild cognitive impairment, and/or ocular disease with onset in childhood or adolescence. Their brain MRIs show mainly confluent signal abnormalities in the periventricular and deep white matter and bilateral thalami. This recognizable pattern of MRI abnormalities is seen in all six adults described here. Biallelic variants in HMBS cause a phenotype that is distinct from AIP. It is not known whether AIP treatments benefit individuals with HMBS ‐related leukoencephalopathy. One individual reported here had improved neurological function for 12 months following liver transplantation followed by decline and progression of disease.